Industry’s recognition to UMP Japanese language teacher - Muhammad Azli, Shukri (Pejabat Naib Canselor, 2016)
Universiti Malaysia Pahang (UMP) Japanese language teacher, Mohd Iszuani Mohd Hassan, was appointed as a member of the International Language Education Panel of Thinkers and Expert Reference by ISMA Holidays Sdn. Bhd.